From the Buffer Layer to Graphene on Silicon Carbide: Exploring Morphologies by Computer Modeling - Bellucci, Luca; Cavallucci, Tommaso; Tozzini, Valentina (Frontiers in Materials, 2019)
Epitaxial graphene grown by thermal Si decomposition of Silicon Carbide appears in different morphological variants, depending on the production conditions: the strongly rugged buffer layer, retaining a considerable amount of sp3 hybridized buffer layer, the softly corrugated graphene monolayer and the rather flat quasi free standing monolayer with sparse small pits pinned to localized electronic states. Therefore, graphene on SiC is not a single material, but a set of materials with different morphologies depending on the environmental conditions during the synthesis. In all cases the distortion from the ideal flat structure seem to follow to some extent specific symmetries, which appear to preserve some memory of the interaction with the SiC bulk, even in the cases in which the sheet is substantially decoupled from it. Defects bear interesting properties, e.g. localized hot spots of reactivity and localized electronic states with specific energy depending on their nature and morphology, while their possible symmetric location is an added value for applications. Therefore, being capable of controlling the morphology, concentration, symmetry and location of the defects would allow tailoring this material for specific applications. Based on ab initio calculations and simulations, we first describe in detail the morphology of the different systems, and, subsequently, we formulate hypotheses on the relationship between morphology and the formation process. We finally suggest future simulation studies capable of revealing the still unclear steps. These should give indication on how to tune the environmental conditions to control the final morphology of the sample and specifically design this material.